Malulo Tradition in the Wedding Ceremony of Tolaki People in North Kolaka Perspective of Urf - Febrianti, Febrianti; Abubakar, Achmad; Abdul Syatar; Kurniati, Kurniati; Syarif, Muhammad Fazlurrahman (Institute of Education and Social Research, 2024)
Malulo, a traditional dance of the Tolaki people, is integral to various religious and social activities such as harvests, weddings, and aqiqah. This research explores the cultural significance of the Malulo dance in Kecamatan Lambai, Kabupaten Kolaka Utara, and examines its alignment with Islamic values, particularly regarding interactions between men and women. The study addresses whether the physical contact in the dance contradicts Islamic teachings and offers solutions to preserve the tradition while adhering to religious principles. Using a qualitative approach, interviews with religious leaders, cultural practitioners, and community members were conducted, alongside an analysis of Islamic legal perspectives on urf (customs). The findings show that while Malulo fosters community cohesion and has deep cultural roots, the practice of hand-holding between non-mahram men and women is seen as inconsistent with Islamic teachings. The research suggests modifications, such as separating men and women during the dance, to preserve the tradition without violating religious values. The study's originality lies in its attempt to reconcile a local cultural tradition with Islamic jurisprudence, offering a balanced solution that respects both heritage and religious principles. This approach highlights the broader importance of harmonizing cultural practices with religious norms, particularly in multi-ethnic and multi-religious societies, and could serve as a model for resolving similar conflicts elsewhere.